2019
DOI: 10.1002/jlb.2mr1218-501r
|View full text |Cite
|
Sign up to set email alerts
|

Role of ADAM17 as a regulatory checkpoint of CD16A in NK cells and as a potential target for cancer immunotherapy

Abstract: Human NK cell antitumor activities involve Ab‐dependent cell‐mediated cytotoxicity (ADCC), which is a key mechanism of action for several clinically successful tumor‐targeting therapeutic mAbs. Human NK cells exclusively recognize these Abs by the Fcγ receptor CD16A (FcγRIIIA), one of their most potent activating receptors. Unlike other activating receptors on NK cells, CD16A undergoes a rapid down‐regulation in expression by a proteolytic process following NK cell activation with various stimuli. In this revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(80 citation statements)
references
References 98 publications
(239 reference statements)
1
65
0
1
Order By: Relevance
“…It is interesting to suggest that additional ligands [e.g., PVR and NKp30 ligands (232)] that are shed by cancer cells may also be targeted in a similar fashion to increase ADCC. Moreover, studies focused on CD16-mediated-killing demonstrate that CD16 undergoes significant proteolytic downregulation following activation (251). CD16 shedding is regulated through metalloproteases such as ADAM17 (252,253).…”
Section: Mabs In Pre-clinical Development-targeting Tumor Antigens Fomentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to suggest that additional ligands [e.g., PVR and NKp30 ligands (232)] that are shed by cancer cells may also be targeted in a similar fashion to increase ADCC. Moreover, studies focused on CD16-mediated-killing demonstrate that CD16 undergoes significant proteolytic downregulation following activation (251). CD16 shedding is regulated through metalloproteases such as ADAM17 (252,253).…”
Section: Mabs In Pre-clinical Development-targeting Tumor Antigens Fomentioning
confidence: 99%
“…This mechanism may serve to facilitate NK cell detachment from targets and thereby increase their mobility (254). Inhibition of CD16 shedding through ADAM17 blockade may increase NK cell activation in the TME, thereby potentiating antibody treatments targeting NK cells (251,255,256). Sustaining this CD16 mediated activity may be especially important, as the Cerwenka group showed that NK cell engagement through CD16 might prime NK cells against cancers by providing them with memory-like effects (257).…”
Section: Mabs In Pre-clinical Development-targeting Tumor Antigens Fomentioning
confidence: 99%
“…Further, NK cells from patients treated with rituximab showed a CD16 downregulation that could last up to 48 hours post infusion [214]. In line with this observation, CD16 stimulation may induce either receptor internalization or shedding on NK cells via ADAM17 [214,215]. Along these lines, strategies targeting tumor ADAMs may synergize with ADCC, although it is still debated whether ADAM17-mediated CD16 cleavage could induce NK cell detachment from the target cell and eventually favor tumor escape.…”
Section: Immunosuppressionmentioning
confidence: 74%
“…In particular, ADAM17 is a potential source of deregulation in the tumor microenvironment and adds an additional level of complexity to the manipulation of these natural systems, which also results in the resistance to chemo-/radiotherapy via the targeted signaling activation (45,46). ADAM17 can be considered as the therapeutic targeting when over activated in the tumor cells either alone or in combination with other treatment, including chemotherapy and radiotherapy (47,48). On the other hand, ADAM17 was discovered as a crucial mediator of resistance to radiotherapy, which can be considered as a therapeutic target when it overexpresses in tumor cells either alone or in combination with other immune modulating treatment.…”
Section: Discussionmentioning
confidence: 99%